FENOMENA PENGGUNAAN BAHASA NONVERBAL DALAM DAKWAH KULTURAL - Warastuti, Rahma Dini (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2014)
The current social situation shows social problems and deviant behavior. In such condition, Allah gives rules, which contain His commands and prohibitions, and asks people to do according to Allah’s rules, and to avoid from what He forbids. From this condition, Islamic preach (da’wah) is needed, which promotes Islamic shari’ah covering all aspects of life. Therefore, Islamic da’wah demands a myriad of approaches, methods, media, message,  actors and partners of  da’wah. From  this,  cultural da’wah model emerged, by which those who were not categorised as a preacher are excited to preach through non-verbal language, such as giving a  good example,  wisdom,  community empowerment, and so forth. This kind of da’wah is proved to be quite effective and successful.